6.2k views
2 votes
Help with #7 please I don’t understand

Help with #7 please I don’t understand-example-1
User Jander
by
5.3k points

2 Answers

1 vote
so your answer is A.
Help with #7 please I don’t understand-example-1
User Kazuaki
by
5.7k points
5 votes

Answer:

A

Explanation:

(2x^2 + 3x - 4) (x + 4)


FOIL.


2x^2 times x = 2x^3

3x times x is 3x^2

-4 times x = -4x

2x^2 times 4 = 8x^2

3x times 4 = 12 x

-4 times 4 = -16


Combine like terms to get 2x^3 + 11x^2 + 8x - 16.

User Rmhrisk
by
4.9k points